Addendum to the AAPMˈs TG‐51 protocol for clinical reference dosimetry of high‐energy photon beams. Issue 4 (12th March 2014) - McEwen, Malcolm; DeWerd, Larry; Ibbott, Geoffrey; Followill, David; Rogers, David W. O.; Seltzer, Stephen; Seuntjens, Jan
Abstract : An addendum to the AAPMˈs TG‐51 protocol for the determination of absorbed dose to water in megavoltage photon beams is presented. This addendum continues the procedure laid out in TG‐51 but new k Q data for photon beams, based on Monte Carlo simulations, are presented and recommendations are given to improve the accuracy and consistency of the protocolˈs implementation. The components of the uncertainty budget in determining absorbed dose to water at the reference point are introduced and the magnitude of each component discussed. Finally, the consistency of experimental determination of N D, w coefficients is discussed. It is expected that the implementation of this addendum will be straightforward, assuming that the user is already familiar with TG‐51. The changes introduced by this report are generally minor, although new recommendations could result in procedural changes for individual users. It is expected that the effort on the medical physicistˈs part to implement this addendum will not be significant and could be done as part of the annual linac calibration.